PTH-189 Double Balloon Enteroscopy in the Elderly with Obscure GI Bleeding- is it Worth the Push and Pull?. (4th June 2013) - Sidhu, R; Hardcastle, S; Sanders, D S
Abstract : Introduction: Double Balloon enteroscopy (DBE) is an increasingly important procedure particularly in the context of obscure GI bleeding (OGB) with a high reported diagnostic yield. There is however paucity of data on its use in the elderly. The aim of this study was to assess the utility of DBE in the elderly and risk of complications compared to a younger cohort. Methods: A prospective review of consecutive patients who underwent DBE over the last six years for the indication of OGB was conducted. The majority of patients underwent a capsule endoscopy prior to DBE, either locally or at our centre. Data was collected on demographics, procedure duration, dose of sedation/analgesia, diagnostic yield and subsequent change in management and complications encountered. Patients were divided into group 1: age≥ 70 years, group 2: age < 70 years. Results: One hundred and forty eight DBE procedures were carried out for the indications of OGB. The majority were for the indication of iron deficiency anaemia (IDA, n = 109.74%), 53% were males and the oral route was carried out in 69% of patients. Group 1 (age≥ 70 years) consisted of 27% (n = 40) of the cohort with a mean age of 77 years (range 70–83 years). There were 38% of patients with the presence of significant co-morbidity and four patients were on warfarin. The diagnostic yield in Group 1 was 53%. There was no significant difference in the yield between those with IDA and overt bleeding (p = 0.7). The commonest diagnosis in the elderly was angioectasia (45%, n = 18). The other findings included a small bowel tumour and mantle cell lymphoma (n = 2) and a Meckels diverticulum (n = 1). Therapeutics was performed in 45%. There was one respiratory arrest in a patient with known chronic airways disease (COPD). This patient was subsequently discharged home after a short stay on intensive care. The mean age in group 2 (n = 108) was 54 years, 44% females and the diagnostic yield was 35%. Comparison of the two groups demonstrated a trend towards a higher diagnostic yield in the elderly (p = 0.06). On logistic regression, previous transfusion requirement was associated with a higher yield with DBE in all patients (p = 0.04).Subsequent management was altered in a significant greater proportion of the elderly (28% versus 50%, p = 0.01, OR 2.6, 95% CI 1.2–5.5). There was no difference in the duration of the procedure between the two groups (p = 0.4), whilst the median dose of midazolam and fentanyl was significantly greater in group 2 (4.5 mg versus 6 mg, p < 0.001, 50mcg versus 75mcg, p < 0.001 respectively).There were no complications in group 2. Conclusion: DBE has a high diagnostic yield with a positive impact on patient management in the elderly. Albeit low rate of complications, careful selection of patients would help reduce risks in this age group. Disclosure of Interest: None Declared.